2007
DOI: 10.1074/jbc.m610033200
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Determinants Involved in Anandamide-induced Inhibition of T-type Calcium Channels

Abstract: Anandamide, originally described as an endocannabinoid, is the main representative molecule of a new class of signaling lipids including endocannabinoids and N-acyl-related molecules, eicosanoids, and fatty acids. Bioactive lipids regulate neuronal excitability by acting on G-protein-coupled receptors (such as CB1) but also directly modulate various ionic conductances including voltage-activated T-type calcium channels (T-channels). However, little is known about the properties and the specificity of this new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 68 publications
6
61
0
1
Order By: Relevance
“…3 and 4). Similar effects of lipoamino acids and arachidonic acid, a product of fatty acid amide hydrolase (FAAH) hydrolysis of NAGly (Grazia Cascio et al, 2004), on ion channel function have been documented (Chemin et al, 2007;Guo et al, 2008a;Barbara et al, 2009). However, it is unlikely that the effects observed in this study are a result of NAGly breakdown to arachidonic acid and glycine because arachidonic acid reduces N-type Ca 21 channel amplitude (Liu and Rittenhouse, 2000) and the effect of NAGly on T-type Ca 21 channels is independent of FAAH activity (Barbara et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…3 and 4). Similar effects of lipoamino acids and arachidonic acid, a product of fatty acid amide hydrolase (FAAH) hydrolysis of NAGly (Grazia Cascio et al, 2004), on ion channel function have been documented (Chemin et al, 2007;Guo et al, 2008a;Barbara et al, 2009). However, it is unlikely that the effects observed in this study are a result of NAGly breakdown to arachidonic acid and glycine because arachidonic acid reduces N-type Ca 21 channel amplitude (Liu and Rittenhouse, 2000) and the effect of NAGly on T-type Ca 21 channels is independent of FAAH activity (Barbara et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Certain cannabinoid receptor agonists (Table 7) and antagonists have been found to antagonize T-type voltage-gated calcium channels at concentrations in the mid-nanomolar or low micromolar range. Thus, for example, evidence has been obtained (Chemin et al, 2001(Chemin et al, , 2007Ross et al, 2008Ross et al, , 2009 It is noteworthy that the phytocannabinoid cannabidiol has also been found to inhibit cloned Ca V 3.1, Ca V 3.2, and Ca V 3.3 calcium channels, its reported IC 50 values for this inhibition being 813, 776, and 3631 nM, respectively (Ross et al, 2008). In addition, a recent article reported that the endogenous lipo-amino acids, NAGly and N-arachidonoyl GABA, can potently inhibit Ca V 3.1, Ca V 3.2, and Ca V 3.3 channels (IC 50 Ͻ1.0 M) (Barbara et al, 2009).…”
Section: F Other Ion Channelsmentioning
confidence: 99%
“…These molecules include arachidonic acid, v3-fatty acids, endocannabinoids (as anandamide), lipo-amino-acids and lipo-neurotransmitters (Zhang et al, 2000;Chemin et al, 2001Chemin et al, , 2007Talavera et al, 2004;Danthi et al, 2005;Barbara et al, 2009;Ross et al, 2009;Gilmore et al, 2012). These lipids are implicated in multiple physiologic functions and more specifically in pain perception (Bradshaw and Walker, 2005;Burstein, 2008;Basbaum et al, 2009), sleep and epilepsy (Chen and Bazan, 2005), and heart rhythm and vasodilatation (Roman, 2002;Leaf et al, 2003).…”
mentioning
confidence: 99%